Uma história da educação matemática em Tangará da Serra – MT (1974 – 1999): formação, currículo e docência - Stascovian, Juliana (Universidade do Vale do Rio dos Sinos, 2025)
The research depicts mathematics teaching in the municipality of Tangará da Serra, Mato Grosso, from 1974 to 1999. Documentary sources and testimonials from ten teachers who taught during this period were collected, with the initial year defined as the first work experience reported during the interview and ending with the completion of higher education by three subjects who did not yet have such training. The research question is: how was mathematics teaching structured in the municipality of Tangará da Serra between 1974 and 1999? In order to answer the question and examine the existing school mathematics culture at the time, the investigations covered the teachers' training, whether initial or continuing; available teaching materials; resources implemented by professionals; teaching strategies; structures offered for the development of the function; current legislation; school routine; student profile and school community. The methodology is anchored in Oral History with Alberti (2004, 2008, 2013) and Thompson (2002), theoretically supported by the concepts of: memory – Fischer (2005, 2011), Halbwachs (1990), and Pollak (1992); school culture – Escolano Benito (2017) and Julia (2001); history of school subjects – Chervel (1990); document and memory – Le Goff (2003) and Cellard (2012); tactics and strategies – Certeau (2014); History of Mathematics Education – Garnica and Souza (2012), Miguel and Miorim (2002, 2012) and Valente (2009, 2013); Mathematics and Education – Machado (2002); professional training – Tardif (2014). The oral and written documents provided evidence of efforts to promote training in projects such as Logos II, in secondary education, established by the Federal Government, and the Distance Learning Undergraduate Courses offered by UNEMAT to teachers in service. Continuing education has grown over the years, as have teachers' initiatives to teach mathematics, which emerged from the subjects' memories and materials, as well as from other localized sources. Continuing education has grown over the years, as have teachers' initiatives to teach mathematics that emerged from the subjects' memories and materials, as well as other localized sources.
Keywords: Formação de professores; Ensino de Matemática; história oral; História da Educação Matemática; Teacher training; Mathematics education; Oral history; History of Mathematics Education; ACCNPQ::Ciências Humanas::Educação